1996
DOI: 10.1185/03007999609111558
|View full text |Cite
|
Sign up to set email alerts
|

Topical therapy of allergic rhinitis in childhood: Allergodil nasal spray -non-sedating in children

Abstract: The efficacy and safety of the nasally administered drug Allergodil in the treatment of allergic rhinitis were evaluated in a prospective drug monitoring programme conducted in Germany. Data from 489 children under the age 13 were included. The study was designed to gain knowledge about Allergodil in a normal clinical setting. Dosing was at the judgement of the investigator bearing in mind data sheet recommendations, i.e. one spray-puff (0.14 mg) per nostril twice daily. Patients were treated for four weeks. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In animal models azelastine has shown to have only poor access to the CNS [14,15]. In clinical studies with azelastine sedation was slightly more frequently reported than after placebo [16−19], whereas in other trials sedation was not reported at all [20,21]. On the other hand, somnolence and fatigue have been reported as two of the most commonly occurring adverse events with intranasal levocabastine [6].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models azelastine has shown to have only poor access to the CNS [14,15]. In clinical studies with azelastine sedation was slightly more frequently reported than after placebo [16−19], whereas in other trials sedation was not reported at all [20,21]. On the other hand, somnolence and fatigue have been reported as two of the most commonly occurring adverse events with intranasal levocabastine [6].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, azelastine HCl is well tolerated; however some commonly reported adverse events associated with the use of intranasal azelastine include irritation of the nasal mucosa and application site (e.g. Grossman et al ., 1994; Lassig et al ., 1996; Mösges et al ., 1995; Wober et al ., 1997), and nasal burning (e.g. Lumry et al ., 2007; Newson‐Smith et al ., 1997; Table 6).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its ability to relieve sneezing; postnasal drip; rhinorrhea; cough; conjunctival symptoms; and itching of the nose, eyes, ears, throat, and palate in 93% of patients between 6 and 11 years of age as a consequence of its histamine antagonism, it also is able to reduce the influx of inflammatory cells into the nasal mucosa and block the release of several mediators [43,44]. Two are now available, levocabastine and azelastine, both of which possess anti-inflammatory activities.…”
Section: Pharmacotherapymentioning
confidence: 99%